POLA ASUH ORANG TUA DALAM PEMBENTUKAN KARAKTER ANAK MELALUI PEMBELAJARAN HIKMAT DARI SEMUT MENURUT AMSAL 6:6-11 - Siburian, Rudi; Tampilang, Petra Harys Alfredo; Simbolon, Andreas Kongres P. (STT-RAI Batam, 2024)
The book of Proverbs is a collection of wise sayings or wisdom that should be pondered and applied in life. Wisdom itself can be obtained through learning from teachers of wisdom and the upbringing and example of parents and by living wisely, one should have a better life, and achieve success. But what happens in Proverbs 6:1-11 is the opposite, the child becomes entangled in his words (verse 2), falls into the grasp of others or debt (verse 3), is labeled lazy (verse 6) and finally becomes poor (verse 11). Looking at the above problems, the question arises: